Implementation of School Adaptation in Distance Learning During the Covid-19 Pandemic - Anggraini, Ulva Kasmarantina; Fitria, Happy; Mulyadi, Mulyadi (Graduate Program Magister Manajemen Pendidikan, 2022)
This study was conducted to know and analyze the process of implementing school adaptation distance learning during the covid-19 pandemic and factors supporting and inhibiting the implementation of school adaptation in implementing distance learning during the covid-19 pandemic. In this study, the research method used is the qualitative descriptive analysis method. The data collected was obtained from 30 correspondents from SMA Negeri Kayuagung in Ogan Komering Ilir district using observation, interview, and documentation. The results showed that the adaptation of schools in implementing distance learning during the Covid-19 pandemic is quite good because of the decisive role of each element involved in its implementation. There were no significant obstacles during school adaptation in implementing distance learning during the Covid-19 pandemic. The skills in using e-learning applications are still low, which are inhibiting factors, so additional training is needed in order to maximize the e-learning system. The supporting factors such as the availability of the Whatsapp application, which can be utilized optimally by many types of users, is the best way to overcome the inhibiting factors in the school adaptation process to implement distance learning during the Covid-19 pandemic.